ASOSIASI FUNGI MIKORIZA ARBUSKULA PADA AVICENNIA SPP - tian, Gus; hanuddin, Bur; Herawatiningsih, Ratna (JURNAL HUTAN LESTARI, 2015)
The symbiosis between Arbuscular mycorrhizal fungi (AMF) and mangrove plant Avicennia spp species was investigated in Terusan Mempawah Hilir.  This research was carried out for 4 months in the Terusan Mempawah Hilir and Laboratory of Silviculture,Faculty of Forestry,Tanjungpura University.  Sampling of soil and roots in the Terusan by observation AMF and conducted by taking samples of soil and roots with techniques lanes at 3 lanes observation. AMF were mostly found in the form of hyphae and were commonly associated with all the mangrove plant Avicennia spp species investigated.  Nine AMF species belonging to the genera Glomus, Gigaspora and Acaulosporawere identified.  The species are Glomus sp1, Glomus sp2, Glomus sp3, Glomus sp4, Glomus sp5, Glomus sp6, Gigaspora sp1, Gigaspora sp2 and Acaulospora sp1.  Spore density of arbuscular mycorrhizal fungi on Avicennia spp stands are 12-97 spores/100 g soils sample and total number of spore are 443 spores. Key word : Avicennia spp, Mycorrhizal, Mangrove, Terusan